Epidemiology of acute myeloid leukemia in Virginia: Excellent survival outcomes for patients in rural Appalachia. Issue 4 (9th March 2021) - Isaac, Krista M.; Reed, Daniel R.; Desai, Raj Piyush; Williams, Eli; Balkrishnan, Rajesh; Keng, Michael K.; Ballen, Karen K.
Abstract: Background: Acute myeloid leukemia, the most common acute leukemia in adults, has a poor overall survival. Studies have suggested that certain socioeconomic factors such as living in a rural or farming area are associated with worse outcomes. Since 42% of acute myeloid leukemia patients seen in our academic center reside in a rural area, we have a unique opportunity to study outcomes of patients in rural versus urban settings. Aim: This analysis evaluates the effect of geography and socioeconomic factors on the biology, treatment, and overall survival of patients with acute myeloid leukemia, with the goal of understanding health care disparities. Methods and results: Patient characteristics, cytogenetic data, treatment history, and overall survival were collected and analyzed to identify differences between urban and rural residency. This cohort included 42% of patients who resided in a rural area at the time of acute myeloid leukemia diagnosis. There was no difference in overall survival between the cohorts. The 1 year overall survival for the entire cohort was 47.9%. There was no difference detected in rates of adverse cytogenetics between the rural and urban cohorts. Similar numbers of patients received induction chemotherapy or proceeded to allogeneic stem cell transplant between the cohorts. Conclusions: This study highlights that similar outcomes can be achieved in rural and urban patients, suggesting that intensive efforts at telehealth, education, and collaboration with local oncology practices may be beneficial.